Intra-carotid arterial administration of autologous peripheral blood-derived endothelial progenitor cells improves acute ischemic stroke neurological outcomes in rats. (15th December 2015) - Chen, Yung-Lung; Tsai, Tzu-Hsien; Wallace, Christopher Glenn; Chen, Yi-Ling; Huang, Tien-Hung; Sung, Pei-Hsun; Yuen, Chun-Man; Sun, Cheuk-Kwan; Lin, Kun-Chen; Chai, Han-Tan; Sheu, Jiunn-Jye; Lee, Fan-Yen; et al.
Abstract: Objective: We tested the hypothesis that transfusion of autologous peripheral blood-derived endothelial progenitor cells (PBDEPC) via the internal carotid artery could reduce brain-infarct zone (BIZ) and neurological deficit in rats following acute ischemic stroke (IS) induced by 50-min left middle cerebral artery occlusion. Design: Adult male Sprague–Dawley rats (n = 60) were equally divided into group 1 [sham control (SC)], group 2 [SC-PBDEPC (5.7 × 10 6 /kg)], group 3 (IS), group 4 [IS-low-dose PBDEPC (1.7 × 10 6 /kg)], group 5 [IS-high-dose PBDEPC (5.7 × 10 6 /kg)]. Groups 2 to 5 received G-CSF (35 μg/kg subcutaneously) for 4 days before drawing blood for PBDEPC culture. Measurements and main results: By day 90, BIZ determined by histopathology (area) and brain MRI (volume) were highest in group 3, lowest in groups 1 and 2, higher in group 4 than in group 5 (all p < 0.0001), and not significantly different between groups 1 and 2. Sensorimotor functional results exhibited an opposite pattern of BIZ among groups 3 to 5 (p < 0.005). Angiogenesis biomarkers (SDF-1α, CXCR4, VEGF, angiopoietin-1) significantly increased progressively from groups 1 and 2 to group 5 (all p < 0.0001). Oxidative-stress (NOX-1, NOX-2, oxidized protein), apoptotic (cleaved caspase 3 and PARP, mitochondrial Bax), inflammatory (MMP-9, TNF-α, AQP-4, GFAP, iNOS), and brain-damaged (cytosolic cytochrome-C) biomarkers showed an identical pattern, whereas anti-inflammatory (Bcl-2), mitochondrial preservation (mitochondrial cytochrome-C, PGC-1α), and endothelial function (CD31 +, vWF +, eNOS) biomarkers, and vessel density showed an opposite pattern of BIZ among these five groups (all p < 0.001). Conclusion: Higher-dose was superior to lower-dose EPC treatment for reducing BIZ and improving neurological functional outcome.